2011
DOI: 10.1111/j.1360-0443.2011.03505.x
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarette: users profile, utilization, satisfaction and perceived efficacy

Abstract: Aims To assess the profile, utilization patterns, satisfaction and perceived effects among users of electronic cigarettes ('e-cigarettes'). Design and Setting Internet survey in English and French in 2010. Measurements Online questionnaire. Participants Visitors of websites and online discussion forums dedicated to e-cigarettes and to smoking cessation. Findings There were 3587 participants (70% former tobacco smokers, 61% men, mean age 41 years). The median duration of electronic cigarette use was 3 months, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
558
4
20

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 601 publications
(624 citation statements)
references
References 24 publications
40
558
4
20
Order By: Relevance
“…Whilst surveys and small scale clinical studies suggest successful replacement of smoking with e-cigarettes due to the presence of nicotine (Dawkins et al, 2013;Etter & Bullen, 2011;Polosa et al, 2011;Siegel, Tanwar & Wood, 2011), effects of vaping on blood nicotine levels are relatively unexplored. In the current study, a significant increase in plasma nicotine level was observed 10 mins after taking 10 puffs on the e-cigarette (from 0.74 ng/ml to 6.77 ng/ml).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst surveys and small scale clinical studies suggest successful replacement of smoking with e-cigarettes due to the presence of nicotine (Dawkins et al, 2013;Etter & Bullen, 2011;Polosa et al, 2011;Siegel, Tanwar & Wood, 2011), effects of vaping on blood nicotine levels are relatively unexplored. In the current study, a significant increase in plasma nicotine level was observed 10 mins after taking 10 puffs on the e-cigarette (from 0.74 ng/ml to 6.77 ng/ml).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst surveys of users and small scale clinical studies suggest their potential for smoking cessation and harm 4 reduction (Caponneto et al, 2013;Dawkins et al, 2013;Etter & Bullen, 2011;Polosa et al, 2011) their ability to deliver nicotine is under-explored.…”
Section: Introductionmentioning
confidence: 99%
“…A 15‐minute break between the 2 exposure sessions was given so that the animals could access fresh air, food, and water. The puff duration was 3 seconds, puff interval 1 minute, and the puff volume was 50 mL, all of which mimics real‐life exposure scenarios 24, 25, 26, 27, 28, 29, 30, 31, 32, 33. As for the controls or control mice, they were matched in terms of age and sex (ie, 10‐week‐old males), and were exposed to clean air.…”
Section: Methodsmentioning
confidence: 99%
“…7,8 However, longitudinal analysis using population-level data found no difference in quit rates between e-cigarette users and nonusers. 9 Controlled clinical trials and populationlevel observational cohort studies are needed to establish the utility of these cigarettes to facilitate smoking cessation.…”
Section: Potential Health Benefits For Individual Smokersmentioning
confidence: 99%